Placental Vitamin D, Oxidative Stress, and Senescence Markers in Spontaneous Preterm Birth: A Comparative Cross-Sectional Study - Saroyo, Yudianto Budi; Wibowo, Noroyono; Prasmusinto, Damar; Purwosunu, Yuditiya; Irwinda, Rima; Dilmy, Mohammad Adya Firmansha; Putri, Atikah Sayogo; Mahendra, Arya Ivan; Putri, Lysandra Olivia Prasanti (Indonesian Journal of Obstetrics and Gynecology, 2026)
AbstractObjective: To evaluate the associations between vitamin D metabolism markers and biomarkers of oxidative stress and placental senescence among women with spontaneous preterm labor compared with those with term labor. Methods: We conducted a comparative cross-sectional study between 2017 and 2019 in two hospitals in Jakarta, Indonesia. Maternal serum and placental samples were collected from women with term labor and spontaneous preterm labor. Markers of the vitamin D pathway 25-hydroxyvitamin D (25[OH]D), 1,25-dihydroxyvitamin D? (1,25[OH]?D?), vitamin D receptor (VDR), and CYP27B1 along with oxidative stress (8-hydroxy-2--deoxyguanosine [8-OHdG]) and placental senescence markers (GLB1 and HMGB), were measured using ELISA, LC–MS/MS, and ICP–MS. Between-group comparisons were performed using parametric or nonparametric tests, as appropriate, and correlations were assessed using Pearson’s or Spearman’s correlation coefficients. Results: A total of 67 women were included (term labor, n = 34; spontaneous preterm labor, n = 33), and both groups were vitamin D deficient. Placental 1,25(OH)?D? levels were significantly lower in the preterm group than in the term group (4.58 ± 2.90 vs 5.57 ± 3.50 pg/ng, p = 0.037). Placental VDR levels also differed significantly between groups {21.70 (6.06–73.40) vs 16.48 (1.87–74.67), p = 0.041}. Across all participants, 8-OHdG and placental senescence markers were negatively correlated with placental 25(OH)D and 1,25(OH)?D? levels and positively correlated with placental CYP27B1 and VDR expression. Conclusion: In this comparative cross-sectional cohort, placental vitamin D metabolites were associated with lower levels of oxidative stress and placental senescence biomarkers, whereas VDR and CYP27B1 showed positive associations with these biomarkers. These patterns may reflect compensatory regulatory mechanisms in the context of maternal vitamin D deficiency. These findings are hypothesis-generating and warrant confirmation in prospective studies and mechanistic investigations. Keywords: oxidative stress, placental senescence, spontaneous preterm labor, vitamin D.